2020
DOI: 10.3126/jpan.v9i1.31337
|View full text |Cite
|
Sign up to set email alerts
|

Attitude of Senior Secondary Level Students towards Mental Illness

Abstract:  Introduction: Mental disorders are recognized as a major contributor (12%) to the global burden of disease and are among the most stigmatizing conditions worldwide. The lack of awareness is very evident in Nepal. In this study, we aimed to learn about the attitude of senior secondary level students towards mental illness. Material And Method: Descriptive cross-sectional study was conducted amongst senior secondary level students to investigate about their attitude towards mental illness. We recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
2
3
0
Order By: Relevance
“…The study results showed differences in attitudes between males and females, as about 66.7% of the female group had a positive attitude towards people with MIs. This finding was consistent with that of the Nepalese study (Nepal et al, 2020) but not in line with previous studies conducted in Saudi Arabia (Alsahali, 2021) and Pakistan (Javed et al, 2006). This variation with a study in Pakistan could be due to the fact that it evaluated both university students and…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The study results showed differences in attitudes between males and females, as about 66.7% of the female group had a positive attitude towards people with MIs. This finding was consistent with that of the Nepalese study (Nepal et al, 2020) but not in line with previous studies conducted in Saudi Arabia (Alsahali, 2021) and Pakistan (Javed et al, 2006). This variation with a study in Pakistan could be due to the fact that it evaluated both university students and…”
Section: Discussionsupporting
confidence: 91%
“…Attitudes of adults and adolescents might not be the same. In the Nepalese study (Nepal et al, 2020), the data suggested that sociodemographic factors, such as age, sex, educational level, or previous exposure to patients with mental illnesses, were related to attitudes towards mental illness and those suffering from it, as shown in this study as well.…”
Section: Anaamsupporting
confidence: 72%
See 1 more Smart Citation
“…The display of negative views is partly attributed to the idea that students did not have information about whom to contact if they had depression and were very aware of the stigma of going to see a “professional” ( Burke et al, 2008 ). Nepal et al (2020) noted that the majority of the students studying at the senior secondary level were found to exhibit negative attitudes toward mental illness. Although no variables were found to be contributing toward such perceptions, Sartorius (2007) assert that stigma is one factor that tends to promote negative attitude toward people suffering from mental illness due to the lack of knowledge and misinformation, which subsequently leads to prejudice and discriminatory tendencies.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Education stakeholders such as school teachers, parents as well as mental health professionals should aim at equipping children with appropriate knowledge on mental illness ( Nepal et al, 2020 ), as this would improve their attitude toward mental illness ( Jyothi et al, 2015 ), and hence the subsequent uptake of related services. Thus, the implementation of attitude enhancing programs by launching anti-stigmatizing programs and providing appropriate information to secondary-level school students has been shown to yield positive results ( Del Casale et al, 2013 ).…”
Section: Review Of Literaturementioning
confidence: 99%